PENGARUH KELENGKAPAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BANGUN MANDIRI - Dismawanti Sanda; Stepanus Sandi (Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study is to determine the Influence of Product Completeness and Service Quality on Purchasing Decisions at the Bangun Mandiri store. The method used is associative with a quantitative approach. Namely a method to determine the relationship or influence between two or more variables in this study the data collection method used is the observation method, questionnaire, and documentation method. To determine the positive influence, the analysis instrument used in the study is Multiple Linear Regression Analysis. The research data was obtained by distributing questionnaires to 100 respondents. The results of the study indicate that product completeness does not have a positive effect on purchasing decisions and service quality has a significant positive effect both partially and simultaneously on purchasing decisions at the Bangun Mandiri Store